the Perencanaan Strategi Pemasaran Berbasis Syariah Melalui Pendekatan Marketing Mix Dalam Mengembangkan Wisata Cakra Suramadu: Tourism - Irodatul Hasanah; Abdur Rahman; Dony Burhan (Jurnal Pariwisata Indonesia, 2022)
Cakra Suramadu Tourism is located in Morkepek Village, Labang District. The tourism is a new tour, so it requires creativity and innovation in its development. One way to develop tourism is through marketing. The purpose of this study was to determine the quality of tourism objects and to formulate a marketing strategy plan in developing Cakra Suramadu Tourism through a marketing mix approach. The method used is descriptive qualitative research method. The data collection technique used by the researcher is by using a literature study that is in accordance with the object of research. The results showed that there was no marketing strategy carried out by Cakra Suramadu Tourism. The marketing strategy of Cakra Suramadu Tourism has not been effective because it is influenced by several factors, namely the lack of quality human resources and capital for development. This resulted in the development of the Cakra Suramadu Tourism being hampered. This is due to several factors, namely the lack of quality human resources and capital for development. Based on the result of the analysis, the researcher rekommends a sharia marketing strategy through the Tiktok application. This strategy is a suitable in promoting tourism because currently the Tiktok application is widely used by businesses to carry out digital marketing such as product promotions, tourist attractions or other. Tourism managers should use this marketing strategy and collaborate with the Trunojoyo Madura University in tourism development.